Breuklijnen in de geschiedschrijving van de Jodenvervolging. Een overzicht van het recente Nederlandse debat - I. de Haan (BMGN: Low Countries Historical Review, 2008)
Fault Lines in the Historiography of the Holocaust. A Survey of the Recent Debate in the Netherlands The historiography of the persecution of the Jews in the Netherlands is an excellent example of the dialectics of progress. Soon after 1945, and even sooner than in the surrounding countries, a series of studies on this subject was readily available in the Netherlands in the form of the monumental historiographies of Herzberg, Presser and De Jong. However, during the 1970s, the production of new studies that examined the persecution of the Jews practically ground to a halt. It was only after the 1980s that a new generation of historians emerged who no longer sketched an all-encompassing perspective for the general public but instead applied themselves to thorough empirical studies written in a detached style for a small specialised audience. As a result of this, the historiography of the Holocaust has radically altered in terms of perspective, methodology and function. This article examines what these recent studies of the Holocaust have accomplished. If scientific progress is defined in terms of increased accuracy, analytical thoroughness, and scientific and societal relevance then the study of the Holocaust has certainly achieved this with regard to the first two criteria. However, it is still the case that the persecution of the Jews in the Netherlands is poorly represented at international debates and the implications of these studies of the Holocaust in the context of the history of Europe have hardly been examined at all. The relevance of a lot of the recent work is undisputed from a historiographical perspective. Yet, as a contribution to the image of the Holocaust outside the walls of Academia, the recent historiography has had less success.